2021
DOI: 10.3390/medicina57121368
|View full text |Cite
|
Sign up to set email alerts
|

Does Cement Augmentation of the Sacroiliac Screw Lead to Superior Biomechanical Results for Fixation of the Posterior Pelvic Ring? A Biomechanical Study

Abstract: Background and Objectives: The stability of the pelvic ring mainly depends on the integrity of its posterior part. Percutaneous sacroiliac (SI) screws are widely implanted as standard of care treatment. The main risk factors for their fixation failure are related to vertical shear or transforaminal sacral fractures. The aim of this study was to compare the biomechanical performance of fixations using one (Group 1) or two (Group 2) standard SI screws versus one SI screw with bone cement augmentation (Group 3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A similar biomechanical investigation of cement augmentation of SI screws in osteoporotic bone found significantly less displacement, when compared with the use of one or two SI screws; however, regarding the number of cycles to failure, no significant difference between the groups could be found. 24 Other known disadvantages of cement augmentation are the possible leakage of cement into the fracture gap/spinal canal and cement embolism.…”
Section: Resultsmentioning
confidence: 99%
“…A similar biomechanical investigation of cement augmentation of SI screws in osteoporotic bone found significantly less displacement, when compared with the use of one or two SI screws; however, regarding the number of cycles to failure, no significant difference between the groups could be found. 24 Other known disadvantages of cement augmentation are the possible leakage of cement into the fracture gap/spinal canal and cement embolism.…”
Section: Resultsmentioning
confidence: 99%
“…As in our case, Höch et al [ 64 ] found a significant and sustained reduction in pain postoperatively in older, osteoporotic patients. Biomechanically, cement augmentation also reduces screw loosening in osteoporotic bone, supporting this approach [ 66 ]. In 8 out of 59 osteosyntheses, a transsacral screw fixation was performed, which allows an alternative to the cemented iliosacral screw due to a bilateral anchorage of the screw in the ilium [ 67 ], whereby no difference was found in the outcome in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Before the introduction of this minimally invasive technique, posterior stabilization was performed using posterior and extensive surgical approaches, which are associated with a substantial soft tissue damage [13,14]. Advantages of the iliosacral screw are the minimally invasive surgical technique, the excellent biomechanical characteristics and the safe and effective clinical use [10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%